The academic face of psychoanalysis : (Taylor & Francis, 2007)
Ever since Freud, psychoanalysts have explored the connections between psychoanalysis and literature and psychoanalysis and philosophy, while literary criticism, social science and philosophy have all reflected on and made use of ideas from psychoanalytic theory. The Academic Face of Psychoanalysis presents contributions from these fields and gives the reader an insight into different understandings and applications of psychoanalytic theory. This book comprises twelve contributions from experts in their fields covering philosophy, psychoanalysis, sociology and literary theory. The chapters are divided into three distinct sections: Psychoanalysis, Philosophy, Social science and literary theory.